2019
DOI: 10.1016/j.cell.2018.10.056
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Fidelity Assembly of Influenza A Virus Promotes Escape from Host Cells

Abstract: Highlights d Influenza A virus forms morphologically and compositionally heterogeneous progeny d Heterogeneity is encoded in assembly and can depend on the growth environment d Progeny of individual virions are as variable as the progeny of large populations d Phenotypic variability helps subsets of the population to escape NA inhibitors

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 78 publications
(90 reference statements)
3
75
0
Order By: Relevance
“…In light of the tegument's primary role in manipulating host cells to facilitate virus replication, the multiple layers of structural variability at play in the tegument provide unique opportunities in the context of herpesvirus adaptability. In much the same way that more genetically fluid RNA viruses such as influenza viruses (Harris et al, 2006;Vahey and Fletcher, 2019), filoviruses (Bharat et al, 2011), and coronaviruses (Goldsmith et al, 2004) benefit from heterogeneous compositions to rapidly respond to selective pressures, structural pleomorphism may provide a crucial avenue of diversity in more genetically constrained dsDNA viruses (because of lower mutation rates) like KSHV, resulting in an increase in evolutionary bandwidth. In essence, facing a relative lack of intraspecies genetic diversity (the tradeoff is more viable progeny), adaptability regarding the ability to manipulate hosts is, instead, implemented at a structural level.…”
Section: Catc Binding Implications For Capsid Assembly and Diversitymentioning
confidence: 99%
“…In light of the tegument's primary role in manipulating host cells to facilitate virus replication, the multiple layers of structural variability at play in the tegument provide unique opportunities in the context of herpesvirus adaptability. In much the same way that more genetically fluid RNA viruses such as influenza viruses (Harris et al, 2006;Vahey and Fletcher, 2019), filoviruses (Bharat et al, 2011), and coronaviruses (Goldsmith et al, 2004) benefit from heterogeneous compositions to rapidly respond to selective pressures, structural pleomorphism may provide a crucial avenue of diversity in more genetically constrained dsDNA viruses (because of lower mutation rates) like KSHV, resulting in an increase in evolutionary bandwidth. In essence, facing a relative lack of intraspecies genetic diversity (the tradeoff is more viable progeny), adaptability regarding the ability to manipulate hosts is, instead, implemented at a structural level.…”
Section: Catc Binding Implications For Capsid Assembly and Diversitymentioning
confidence: 99%
“…For example, the cell-to-cell variable viral transcript counts and progeny yields have been observed with influenza, lymphocytic choriomeningitis, arenavirus, foot-and-mouth disease virus, Herpes simplex virus 1, murine gammaherpesvirus 68 and Dengue and Zika virus [10][11][12][13][14][15][16][17]. Studies with Influenza A virus revealed variability in translation and assembly of progeny particles [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, viruses might enter the body from the seawater via the cloaca, replicate in the distal parts of the intestine and again are excreted by feces, as previously suggested (Scholtissek, 1985). Since methods to label influenza virus proteins with fluorophores are now available (Fukuyama et al, 2015;Vahey and Fletcher, 2019) the hypothesis is now amenable to experimental verification by following expression of viral proteins in various tissues and cells after oral infection of birds.…”
Section: Discussionmentioning
confidence: 96%